Chemical Composition, Cytotoxicity, and Encapsulation of Lavender Essential Oil (Lavandula angustifolia) in Alginate Hydrogel—Application and Therapeutic Effect on Animal Model - Michalina Adaszyńska-Skwirzyńska; Yu-Hsiang Yu; Paweł Konieczka; Krzysztof Kozłowski; Dorota Witkowska; Andrzej Dybus; Beata Hukowska-Szematowicz; Magdalena Jędrzejczak-Silicka; Mateusz Bucław; Artur Bartkowiak (Molecules, 2025)
Lavender essential oil (LEO) was analyzed using gas chromatography coupled with a mass selective detector (GC-MS), detecting linalool and linalyl acetate as its major constituents. The biological activity of the LEO was evaluated in vitro using a normal mouse fibroblast cell line (L929), where it showed no cytotoxic effects. To assess its therapeutic effect in vivo, a broiler chicken model (Ross 308) was employed. Birds were divided into three groups: the control group (C) without any hydrogel supplementation; the H group, supplemented with alginate hydrogel capsules without LEO; and the HE groups, which received hydrogel capsules containing immobilized LEO. Capsules were provided on chick paper for voluntary intake from day 1 to day 10. At the end of the production cycle, the cecum was dissected and preserved for subsequent molecular analyses. Results demonstrated that dietary supplementation with alginate hydrogel containing immobilized LEO (HE group) positively influenced the production parameters and intestinal health in broiler chickens. Dietary supplementation with alginate hydrogel-encapsulated LEO exerts therapeutic effects in broilers.